Perancangan Alur Sistem Komputerisasi Pada Sistem Penjaminan Mutu Dan Evaluasi Diri Perguruan Tinggi Swasta - Didik Nugroho (STMIK Sinar Nusantara, 2010)
Global challenges such as universities in Indonesia competitiveness, unemployment, and akuntabilitas of society. Facing the above problems, Universities and colleges should menerpak quality assurance system. With the quality assurance system it is expected that universities can improve their quality gradually. To improve the performance of quality assurance is necessary to utilize information technology as a means of quality assurance managemen.Keywords : quality assurance system, self-evaluation